Development of Mutual Funds in The Indonesian Capital Market - Rizky, Syafnur Muhammad; Andini, Bunga; Hasda, Mifta; Syaipudin, Muhammad; Sudirman, Wahyu Febri Ramadhan (Global Sustainability Research Institute, 2024)
This research examines the development of mutual funds in the context of the Indonesian capital market. Mutual funds have become one of the investment instruments that is increasingly popular and important in diversifying investor portfolios in Indonesia. This research aims to analyze the factors that influence the growth of mutual funds, the role of regulation in regulating the market, and the challenges faced in optimizing the potential of mutual funds as an effective and safe investment instrument. This study uses a descriptive-analytical approach by collecting secondary data from various literature sources related to the development of capital markets and mutual funds in Indonesia. The analysis results show that the growth of mutual funds is influenced by increasing public financial awareness and ease of access to information about investment products. The regulatory role carried out by the Financial Services Authority (OJK) also contributes to creating a more structured and safe investment environment for investors. However, several challenges need to be overcome, such as market fluctuations which can affect investment values, liquidity problems in several types of mutual funds, as well as expanding financial education to the public. Better regulation is needed to address these challenges and increase transparency and protection for investors.